2011
DOI: 10.1016/j.jtbi.2011.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Disease embryo development network reveals the relationship between disease genes and embryo development genes

Abstract: A basic problem for contemporary biology and medicine is exploring the correlation between human disease and underlying cellular mechanisms. For a long time, several efforts were made to reveal the similarity between embryo development and disease process, but few from the system level. In this article, we used the human protein-protein interactions (PPIs), disease genes with their classifications and embryo development genes and reconstructed a human disease-embryo development network to investigate the relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 85 publications
(96 reference statements)
3
4
0
Order By: Relevance
“…Because genes annotated as having a role in embryonic development will have a degree of overlap with essential genes, the results of this analysis are expected to concur with network analysis of essential genes. The authors found a significant association between embryonic development genes and genes associated with human disease (Gong et al, 2011), similar to findings from studies exploring the relationship between essential genes and disease (Dickerson et al, 2011). Both studies also found statistically significant links between genes causing cancer when mutated and essential or embryonic development genes (Dickerson et al, 2011;Gong et al, 2011).…”
Section: Functional Properties Of Essential Genes and Disease Genessupporting
confidence: 76%
See 1 more Smart Citation
“…Because genes annotated as having a role in embryonic development will have a degree of overlap with essential genes, the results of this analysis are expected to concur with network analysis of essential genes. The authors found a significant association between embryonic development genes and genes associated with human disease (Gong et al, 2011), similar to findings from studies exploring the relationship between essential genes and disease (Dickerson et al, 2011). Both studies also found statistically significant links between genes causing cancer when mutated and essential or embryonic development genes (Dickerson et al, 2011;Gong et al, 2011).…”
Section: Functional Properties Of Essential Genes and Disease Genessupporting
confidence: 76%
“…The authors found a significant association between embryonic development genes and genes associated with human disease (Gong et al, 2011), similar to findings from studies exploring the relationship between essential genes and disease (Dickerson et al, 2011). Both studies also found statistically significant links between genes causing cancer when mutated and essential or embryonic development genes (Dickerson et al, 2011;Gong et al, 2011). Thus, genes functioning in embryonic development have a similar network profile and disease association profile as essential genes.…”
Section: Functional Properties Of Essential Genes and Disease Genessupporting
confidence: 76%
“…(26). Similarly, brain development-related genes were also obtained from GO, which were annotated with the term ‘brain development.’ In addition, brain-related miRNAs were collected from several recent reviews.…”
Section: Methodsmentioning
confidence: 99%
“…The disease embryo development network reveals the relationship between disease genes and embryo development genes. An approach based on this network could document the important correlation between disease processes and embryo development, and aid in the understanding of the potential mechanisms of complex human diseases [16]. The term ‘human interactome' has been created to describe this network medicine.…”
Section: Figmentioning
confidence: 99%